RBM10 Deficiency Is Associated With Increased Immune Activity in Lung Adenocarcinoma - Liu, Bing; Wang, Yaqi; Wang, Han; Li, Zhongwu; Yang, Lujing; Yan, Shi; Yang, Xin; Ma, Yuanyuan; Gao, Xuan; Guan, Yanfang; Yi, Xin; Xia, Xuefeng; et al. (Frontiers in Oncology, 2021)
Introduction: Although previous studies have confirmed that RBM10 could suppress the disease progression and cell proliferation in lung adenocarcinoma (LUAD), the association between RBM10 deficiency and anti-tumor immunity have not yet been elucidated. Materials and methods: A systematic analysis was performed based on whole exome sequencing data of 39 tumor samples from early-stage LUADs (GGN cohort) and genomic and transcriptome data of the Cancer Genome Atlas (TCGA) LUAD cohort (TCGA_LUAD cohort) and a Chinese LUAD cohort (CHOICE_ADC cohort). GSEA was used to determine potentially relevant gene expression signature. Mutations were clustered into subclones by using PyClone-0.13.0 and neoantigens were predicted by NetMHCpan-4.0. Immune infiltration levels were estimated by TIMMER and the predicated immunotherapy response was calculated through TIDE algorithm. Results: The mutation rate of RBM10 was significantly higher in GGN cohort than that in TCGA_LUAD and CHOICE_ADC cohorts. In both TCGA_LUAD and CHOICE_ADC cohorts, multiple immune related pathways were markedly enriched in RBM10 deficient group. Further analyses showed that tumors with RBM10 mutations displayed higher TMB and neoantigen levels than wild-type ones, and LUADs with RBM10 deficiency also showed higher HLA expression levels, including many HLA class I and II molecules. Additionally, many immune cells, including myeloid dendritic cells, macrophages, neutrophils and CD8+T cells, showed higher infiltration levels in LUADs with RBM10 deficiency. Finally, some immune checkpoint molecules, such as PD-L1 and TIM-3, were highly expressed in RBM10 deficient population and the predicted immunotherapy response was calculated through TIDE algorithm, showing that IFNG expression, MSI score and CD8 expression were higher in RBM10 deficient group, while MDSC and M2 macrophage were lower in RBM10 deficient group. Conclusion: RBM10 deficiency could enhance anti-tumor immunity in LUAD and patients